FABC (Federation of Asian Bishops’ Conferences): Menghargai dan Menghormati Kelayakan Kemanusiaan Asia – Indonesia - Ignasius Budiono; Edison R.L. Tinambunan (Litbang STFT Widya Sasana Malang, 2022)
One of the central themes discussed both internationally and nationally is about humanity which is identified with human rights. Religiosity is no less talked about it, including the Church of Asia through the Asian Bishops' Conference which in 2020 celebrated its presence for fifty years. Two declarations from the United Nations and the ASEAN declaration provide directions for upholding humanity and the Asian Bishops Conference document provides the basis for humanity to be more honored and respected. To arrive at the aim of discussing the contribution of the Asian Bishops' Conference to respect and honor humanity, the discussion will begin with an overview of humanity from religious and philosophical dimensions. The two United Nations declarations and the ASEAN declaration provide directions for humanity that serve as guidelines for respecting it. The document of the Asian Bishops' Conference, while respecting the declarations issued by various agencies, illuminates the implications for respecting and respecting humanity. This study uses many sources of documents and humanitarian movements in Asia and Indonesia as well and this paper concludes with a conclusion that gives the reason for Asia being the highest violator of humanity in the world.